Management of Extracurricular Activities Shaping the Character of Students in Madrasa - Tursino, Tursino; Fakhri, Jamal (Journal of Advanced Islamic Educational Management, 2021)
The process of fostering students through extracurricular activities has an essential role in shaping the character of students because extracurricular activities are a vehicle for channeling talents and interests that function to develop the potential, abilities, personality, cooperation, and independence of students optimally to support the achievement of goals education. This study aims to obtain a detailed description of (1) Planning extracurricular activities in character building of students, (2) Organizing extracurricular activities in character building of students, (3) Direction of extracurricular activities in character building of students, and (4) Controlling extracurricular activities in shaping the character of students at Madrasa Tsanawiyah Al-Ikhlas Tanjung Bintang. This study uses a qualitative approach with a phenomenological type of research. Data collection techniques are carried out by; participatory observation, in-depth interviews, and document analysis. The data analysis process starts with data reduction, data presentation, and conclusion drawing. Test the validity of the data by triangulation and member check. The results of this study are (1) Planning for extracurricular activities in the formation of students' character is carried out in preparing extracurricular activity programs, which are then used as a reference in its implementation. The program development process is preceded by analyzing the required resources, carried out collaboratively, and socialized at the beginning of the school year. (2) Organizing extracurricular activities in forming students' character as a whole is integrated with the madrasa organization. The organizing process determines resources and division of tasks according to the field of expertise, determined by the Decree of the Head of Madrasa, making agreements to shape students' character through routine activities, such as spontaneous action and conditioning. (3) Extracurricular activities are carried out to ensure that activities focus on the goals that have been set in the planning. The activity direction process includes; application, exemplary leadership, problem-solving, commitment to tasks, functions, and roles, and (4) Control of extracurricular activities to form student character through monitoring, assessment, and reporting. Controls include; monitoring the implementation of activities and evaluating activities (assessment of processes and assessment of results); most students get satisfactory results but still need to improve the readiness of the supporting components.